Doing business in emerging markets : roadmap for success - Goncalves, Marcus. (2014 digital library., 2015)
Reflects the challenges and opportunities facing international businesses and professionals when operating in emerging markets, particularly in the wake of the financial crisis of 2008. This book is filled with valuable information and real-world facts and examples from across the globe. It covers all the key topics on conducting business in emerging markets, addressing important aspects of entering a new market, as well as post-entry issues and strategies, such as dealing with corruption, the application of the United States Foreign Corrupt Practice Act (FCPA), international market research and more, demonstrating how the emerging market context challenges traditional international business theories and even best practices. Marcus Goncalves, Fall 2014.